The Abuse of Guaranteed Pending Trial in the Chinese Criminal Process: A Violation of International Human Rights Law - Enshen, Li (UI Scholars Hub, 2011)
Guaranteed pending trial (Qubao Houshen) is one of the coercive measures used by the Chinese authorities to release suspects on bail in the criminal process. Unlike the western general practices, this instrument is not characterized as a legal right of suspects, but an effective means to circumvent the procedural requirements of investigation and prosecution in the laws. Further, the abuse of guaranteed pending trial is in fragrant violation of minimal international standards of human rights protection in the criminal justice system. The article first examines the procedural and practical deficiencies of this measure in the Chinese context. It then argues that the Chinese authorities ought to reform guaranteed pending trial by bringing it in line with the relevant global norms. To achieve this goal, certain overseas models that have proven consistent with the international criteria of human rights protection are expected to be borrowed. It concludes that the mature western experiences are indeed of benefit to the reconstruction of the regulatory framework of guaranteed pending trial, but their embeddedness should be compatible with the Chinese legal and cultural particularities in order to maximize their adaptability. However, given the Chinese long-standing perception of denying individual human rights, the current guaranteed pending trial system may not be advanced along with the legal reforms, so a genuine bail mechanism is unlikely established in the Chinese criminal process in contemporary China.